2020
DOI: 10.5603/jnns.a2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Huntington’s Disease — a systematic review

Abstract: Introduction. Huntington's Disease (HD) is a neurodegenerative disorder of which the main symptoms are motor, cognitive and behavioural problems sometimes including sexual dysfunction. Aim.To review the current knowledge on sexual dysfunction in HD.Methods. Databases of Pubmed and Scopus were searched. Only original studies performed after 1994 were included (from 1994 a genetic test = proven diagnosis).Results. 162 publications were found, but only nine met our established criteria. The majority of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…6 Depression can also be caused or worsened by dopamine depleting agents used to treat HD chorea. 26 In addition, antidepressants, neuroleptics and benzodiazepine can also cause sexual dysfunction. 26 On the other hand, there is no significant correlation between the international index of erectile function score and the number of CAG repeats in men, 8,9 but a positive correlation between the number of triplets and sexual desire in women.…”
Section: Sexual Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Depression can also be caused or worsened by dopamine depleting agents used to treat HD chorea. 26 In addition, antidepressants, neuroleptics and benzodiazepine can also cause sexual dysfunction. 26 On the other hand, there is no significant correlation between the international index of erectile function score and the number of CAG repeats in men, 8,9 but a positive correlation between the number of triplets and sexual desire in women.…”
Section: Sexual Disordersmentioning
confidence: 99%
“…26 In addition, antidepressants, neuroleptics and benzodiazepine can also cause sexual dysfunction. 26 On the other hand, there is no significant correlation between the international index of erectile function score and the number of CAG repeats in men, 8,9 but a positive correlation between the number of triplets and sexual desire in women. 8,9 Data suggests that sexual dysfunction is correlated with decreased functional capacity measured using TFC and TMS, 8,9 rather than disease duration.…”
Section: Sexual Disordersmentioning
confidence: 99%
“…They found that the majority of patients with HD had sexual disorders, particularly hypo/ hyperactive sexual disorder, erectile and ejaculatory dysfunction, lubrication problems, and orgasmic dysfunction. Their findings suggest that SD is more common in HD and correlates with QoL measures [6]. However, their review also illuminates several limitations of the current literature regarding SDHD.…”
mentioning
confidence: 97%
“…Szymuś et al conducted a systematic review of HD-associated sexual dysfunction [6]. They found that the majority of patients with HD had sexual disorders, particularly hypo/ hyperactive sexual disorder, erectile and ejaculatory dysfunction, lubrication problems, and orgasmic dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation